Isolation, phylogenetics, and characterization of a new PDCoV strain that affects cellular gene expression in human cells - Yang, Xiaozhu; Yin, Hanwei; Liu, Mengyuan; Wang, Xuemei; Song, Tao; Song, Aiai; Xi, Yibo; Zhang, Ting; Sun, Zilong; Li, Wei; Niu, Sheng; Zainab, Farwa; et al. (Frontiers in Microbiology, 2025)
IntroductionPorcine deltacoronavirus (PDCoV) is an enteropathogenic coronavirus that causes acute diarrhea, vomiting, dehydration, and even death in piglets, resulting in serious economic losses to the pork industry worldwide. PDCoV has received much attention owing to its broad host range, including humans, posing a potential threat to public health. However, the prevalence, characteristics, and host cellular gene expression of PDCoV remain poorly understood.MethodsIn this study, a new PDCoV strain (CHN/SX-Y/2023, GenBank number PQ373831) was successfully isolated, identified, and subjected to phylogenetic tree and transcriptome analysis in human hepatoma (Huh7) cells following PDCoV infection.ResultsThe results showed that the CHN/SX-Y/2023 strain belongs to the Chinese lineage and causes cytopathic effects in canonical cell lines (LLC-PK1 and ST cells) and other cell lines (Huh7 and LMH cells). However, HEK-293T, EEC, MDBK, and Vero-CCL81 cells were not found to be susceptible in this study. Based on transcriptome analysis, 1,799 differentially expressed genes (DEGs) were upregulated and 771 were downregulated during PDCoV infection.DiscussionAmong the upregulated genes, FCGR1A, VSIG1, TNFRSF9, and PLCXD3 are associated with immunity, inflammation, and lipid catabolism. Moreover, Kyoto Encyclopedia of Genes and Genomes analysis revealed that the upregulated DEGs were significantly enriched in the MAPK, TNF, and NF-κB signaling pathways and viral protein interactions with cytokines and cytokine receptors. Protein–protein interaction networks showed that the upregulated genes CXCL8, DUSP1, PTGS2, and IL15 were associated with inflammation and immunity. In addition, the protein levels of p-IRF3, LC3-II, and ACSL4 increased, suggesting that PDCoV infection in Huh7 cells induces an intrinsic immune response, cellular autophagy, and ferroptosis. Collectively, our findings provide new insights into the characteristics and mechanisms of PDCoV infection.